Diagnosis of primary ciliary dyskinesia - Olm,Mary Anne Kowal (2015)
Primary ciliary dyskinesia (PCD) is a genetic disorder of ciliary structure or function. It results in mucus accumulation and bacterial colonization of the respiratory tract which leads to chronic upper and lower airway infections, organ laterality defects, and fertility problems. We review the respiratory signs and symptoms of PCD, as well as the screening tests for and diagnostic investigation of the disease, together with details related to ciliary function, ciliary ultrastructure, and genetic studies. In addition, we describe the difficulties in diagnosing PCD by means of transmission electron microscopy, as well as describing patient follow-up procedures.